Serotonergic neurons regulate the Drosophila vascular niche to control immune stress hematopoiesis - Xiaohui Liu; Marianne Montemurro; Nathalie Vanzo; Michèle Crozatier (Nature Communications)
Abstract In adult mammals, hematopoietic stem/progenitor cells reside in the bone marrow, in a specialized microenvironment called a “niche”, which is composed of different cell types, including nerves. Although it is established that sympathetic nerves regulate hematopoiesis, little is known about the role of neural serotonin in bone marrow. The Drosophila hematopoietic organ, the lymph gland, is aligned along the aorta, which corresponds to the vascular niche. Here, we report that serotonin signaling in the vascular niche regulates the hematopoietic response to an immune challenge. The serotonin receptor 1B expressed in vascular niche cells, together with serotonin produced by neurons regulate the degradation of the extracellular matrix of the lymph gland and prevent its premature dispersal after an immune challenge. Serotonin signaling in aorta cells acts via JAK/STAT pathway activation. Our results provide novel insights into how vascular niche cells integrate neural information to regulate lymph gland immune stress hematopoiesis.